Palynology of the Late Triassic Ischigualasto Formation, Argentina: Paleoecological and paleogeographic implications - Cesari, Silvia Nelida (2016)
In this study we describe and compare the palynological assemblages from the Carnian Ischigualasto Formation of westernmost Gondwana to those of eastern Gondwana, which have been referred to the Onslow and Ipswich phytogeographic provinces. The palynofloras studied contain many taxa common to both regions, as well as several species that are widely recorded in European Carnian successions and less frequently recovered in the Carnian of the Southern Hemisphere. For the first time in Argentinean assemblages, we recognize Anapiculatisporites spiniger, Cadargasporites granulatus, Cycadopites stonei, Ellipsovelatisporites plicatus, Enzonalasporites vigens, Ovalipollis pseudoalatus, O. ovalis, Patinasporites densus, Quadraeculina anellaeformis, Samaropollenites speciosus, Staurosaccites quadrifidus, “Rimaesporites” aquilonalis, Vallasporites ignacii and Zonalasporites cinctus. The new evidence extends the distribution of the Onslow palynoflora to include Carnian associations formerly assigned to the Ipswich Province. The affinities of Argentinean palynofloras seem to indicate the existence of a similar flora extending from the northern Australian margin (West Timor), through the western Tethys coasts, to westernmost Gondwana during the Carnian. Moreover, the new data reinforce the close relationship between some diagnostic species and humid environmental conditions.